CLEARING RATING RATE IN DIFFERENT SUBSTRATES ON PURNAMA BEACH WATERS OF DUMAI CITY OF RIAU PROVINCE - Tri Prawoto; Syafruddin Nasution; Musrifin Galib (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Barnacle is one of the marine biota that belongs to the crustacean class and is one of the sub-classes of Wikipedia, whose life is permanently attached to hard objects submerged at sea and has properties that can damage and shorten the life of a building that it occupies. The purpose of this study was to determine the rate of sticking barnacles on wood, concrete and peralata substrates. This research was conducted from January 28 to March 10 2019 in the waters of the Purnama Coast in Dumai City. The method used is the experimental method. The results are the highest rate of barnacle attachment found in wood is 63 ind/week, then the concrete substrate 35 ind/week and the lowest is the 18 ind/week pipe plastic substrate. The highest abundance of barnacles on wood substrates in the 6th week with a value of 25 ind/m2and the lowest abundance of barnacles was found on the paralon substrate in the 6th week with a value of 3 ind/m2. Keywords: barnacles, substrate, attachment rate, abundance, Dumai